High glucose causes dysfunction of the human glomerular endothelial glycocalyx - Anurag Singh; Vincent Fridén; Indranil Dasgupta; Rebecca R. Foster; Gavin I. Welsh; J. E. Tooke; Börje Haraldsson; Peter W. Mathieson; Simon C. Satchell (2010)
The endothelial glycocalyx is a gel-like layer which covers the luminal side of blood vessels. The glomerular endothelial cell (GEnC) glycocalyx is composed of proteoglycan core proteins, glycosaminoglycan (GAG) chains, and sialoglycoproteins and has been shown to contribute to the selective sieving action of the glomerular capillary wall. Damage to the systemic endothelial glycocalyx has recently been associated with the onset of albuminuria in diabetics. In this study, we analyze the effects of high glucose on the biochemical structure of the GEnC glycocalyx and quantify functional changes in its protein-restrictive action. We used conditionally immortalized human GEnC. Proteoglycans were analyzed by Western blotting and indirect immunofluorescence. Biosynthesis of GAG was analyzed by radiolabeling and quantified by anion exchange chromatography. FITC-albumin was used to analyze macromolecular passage across GEnC monolayers using an established in vitro model. We observed a marked reduction in the biosynthesis of GAG by the GEnC under high-glucose conditions. Further analysis confirmed specific reduction in heparan sulfate GAG. Expression of proteoglycan core proteins remained unchanged. There was also a significant increase in the passage of albumin across GEnC monolayers under high-glucose conditions without affecting interendothelial junctions. These results reproduce changes in GEnC barrier properties caused by enzymatic removal of heparan sulfate from the GEnC glycocalyx. They provide direct evidence of high glucose-induced alterations in the GEnC glycocalyx and demonstrate changes to its function as a protein-restrictive layer, thus implicating glycocalyx damage in the pathogenesis of proteinuria in diabetes.